Traceability Approaches for Marine Genetic Resources Under the Proposed Ocean (BBNJ) Treaty - Fran Humphries; Muriel Rabone; Marcel Jaspars (Frontiers in Marine Science, 2021)
Negotiations are underway for a new treaty for the conservation and sustainable use of biodiversity of areas beyond national jurisdiction under the United Nations Convention on the Law of the Sea. Points of contention in the negotiation concern marine genetic resources and questions of monetary and/or non-monetary benefit sharing arising from their use. Tracing the origin of marine genetic resources used in scientific research, development and commercialization may offer the evidence needed to prove they came from areas beyond national jurisdiction and that benefit sharing is owed. Traceability is complex and multidisciplinary: involving legal, scientific and informatics considerations. We look at different traceability approaches within national jurisdictions and how these might provide lessons for the proposed treaty, using one of the few case studies available to trace the commercial development of a marine genetic resource from areas beyond national jurisdiction. We discuss this case study in relation to existing legal frameworks including the Nagoya Protocol and other systems based on open sharing of information and materials, including existing scientific practice. We conclude that a well-designed traceability system tailored to the unique geographical, political and jurisdictional characteristics of areas beyond national jurisdiction could lead to more equitable outcomes for the sharing of benefits from the use of marine genetic resources. Our key recommendations are that any traceability mechanism needs to be light touch, integrated with existing systems such as bioinformatics databases and not impose additional burdens on scientific users. Systems should be designed to improve scientific knowledge of ocean biodiversity to allow better conservation measures to be developed. If treaty negotiators engage commercial sectors to find workable policy solutions for the draft treaty that promote greater transparency and data sharing from these sectors, there may be a greater chance for traceability mechanisms to support benefit sharing.